PENERAPAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) PADA A MAGICAL AUGMENTED REALITY BOOK BERBASIS ANDROID - Agus Kurniasari, Arvita; Trismayanti Dwi Puspitasari; Argista Dwi Septya Mutiara (Universitas Islam Balitar, 2023)
The development of Information and Communication Technology is currently very rapid, so it is either used or utilized in the world of education, which has a positive impact. On the other hand, technology can also hurt children under 6 years of age who are still in developmental stages, such as being lazy to move and not interacting with the outside world, so the desire to learn at school and home will decrease. One example of good learning media for children is Augmented Reality (AR) technology. AR is a technology that combines two-dimensional and or three-dimensional virtual objects into a real three-dimensional environment and then projects these virtual objects in real-time. This AR technology can insert certain information into the virtual world and display it in the real world. AR technology helps to create a moving 3D object. This is the background for making applications that help introduce technology into books with the theme of Suro and Boyo folklore which can be used as learning tools and an introduction to the origins of regions in Indonesia. The Multimedia Development Life Cycle (MDLC) method was implemented in this application. The main target of this application is Kindergarten-aged children, which has been implemented to determine the application acceptance rate of 70%.